Global Burden of Hypertension and Strategic Approach to Overcome It - Hossain, Md Zakir (Bangladesh Journal of Medicine, 2023)
Globally an estimated 1.28 billion people have hypertension, most (two thirds) living in low and middle income countries. It is the leading cause of preventable death and is responsible for 10-20% of all death worldwide. Moreover, untreated hypertension can lead to a number of serious health consequences like stroke, heart disease, renal failure, dementia, vision loss etc. Antihypertensive treatment substantially reduces incidence of stroke (35-40%), myocardial infarction (20-25%) and heart failure (>50%). But hypertension remains undiagnosed in about 46% cases and only about 21% hypertensive individuals have adequately controlled blood pressure. There are several misconceptions regarding hypertension among people that hinders diagnosis or leads to false diagnosis and impair proper management of hypertension. In attempt to reduce burden of hypertension awareness generation is the first necessary step. To create awareness among people several seminar, free blood pressure check-up campaigns etc can be conducted, billboard placement and leaflet distribution can be done in different public gathering sites like bazaar, fairs, mosques, school, college, hospital etc, and necessary knowledge on hypertension can be circulated through primary or secondary school textbooks and printing and electronic media. The next essential step is to provide quality service for hypertensive patients at an affordable cost through dedicated hypertension centers or hypertension corners. These centers should be designed to provide proper training for the stuff and proper education or counseling for patients and to perform necessary research works. Government initiatives to distribute free antihypertensive drugs should be enhanced and non-government aids can be added to it. National policy to control price of antihypertensive medications is also necessary. Finally, regular follow-up is necessary to ensure regular intake of medications, adherence to lifestyle advices, adequate titration of medications and early detection and treatment of any target organ damage. Proper counseling at each visit and reminder through phone calls or mobile SMS can improve follow-up tendency. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 185